MENINGKATKAN KEMAMPUAN MENGENAL LAMBANG HURUF MELALUI MEDIA KARPET HURUF PADA KELOMPOK A DI TK MEKAR SARI TENGGARONG SEBERANG - Tarsiyem - Tarsiyem; Hanita - Hanita (Jurnal Warna : Pendidikan dan Pembelajaran Anak Usia Dini, 2018)
From sixteen students in group A of Mekar Sari Kindergarten Tenggarong Seberang, only two of them recognized letters. Therefore, the researcher conducted a classroom action research to improve students’ ability in recognizing symbols of letters by using letter mat. This study applied two cycle wherein each cycle consists of palnning, implementation, observation and reflection. To gather the data, the researcher employed observation. Meanwhile, to analyze the data, the researcher applied percentage analysis. As the research subjects, the researcher involved sixteen students, consisting of seven males and nine females.At the first cycle, 68,75% students were able to repeat the symbols of letters the teacher mentioned. 68,75% students managed to mention the letter symbols. 62,5% students managed to mention the letters of their own names. 68,75% students were able to mention the letter symbol which teacher mentioned. In other words, in the first cycle, 68,75% students managed to recognize symbols of letter. Moreover, at the second cycle, 100% students were able to repeat the symbols of letters the teacher mentioned. 100% students managed to mention the symbols letter symbols. 87,5% students managed to mention the mention the letters of their own names. 100% students were able to mention the letter symbol which teacher mentioned. It can be concluded that 97,5% students successfully recognized the symbols of letters and were considered able to develop well.In brief, learning letter through letter mat has effectively increased students’ ability in recognizing symbols of letters, especially in group A at Mekar Sari Kindergarten Tenggarong Seberang. Therefore, it is recommended for teachers to use the letter mat for teaching letters.